2003
DOI: 10.1103/physrevlett.91.036803
|View full text |Cite
|
Sign up to set email alerts
|

Signature of a Chemical Bond in the Conductance between Two Metal Surfaces

Abstract: Conductance in monatomic metal contacts is quantized; it increases in discrete steps of one conductance quantum 2e 2 =h. By contrast, in a vacuum barrier between two metal surfaces we find that conductance increases linearly and continuously with the interaction energy between individual atoms. This behavior shows unambiguously that current flow between single atoms is a measure for their chemical interaction. In the controlled environment of a scanning tunneling microscope it should allow us to study the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 25 publications
3
40
1
Order By: Relevance
“…The solution, for gold surfaces, was presented by Hofer et al [19]; it involved calculating the forces and relaxations of coupled systems, and to determine the effect on constant current contours within a firstprinciples approach. It was also shown that tunneling current and interaction energy are in fact proportional to each other [20]. This result, contradicting earlier assumptions by Chen [21], is confirmed by experimental data [22].…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The solution, for gold surfaces, was presented by Hofer et al [19]; it involved calculating the forces and relaxations of coupled systems, and to determine the effect on constant current contours within a firstprinciples approach. It was also shown that tunneling current and interaction energy are in fact proportional to each other [20]. This result, contradicting earlier assumptions by Chen [21], is confirmed by experimental data [22].…”
contrasting
confidence: 53%
“…We then introduced interaction forces and the induced relaxations in the following way. Assuming that the interaction energy E is given by E = ÀaG, where G is the tunneling conductance and a a constant, which is determined by first principles simulations [20], then the vertical relaxation of surface atoms z can be determined within the harmonic approximation by E = Àkz 2 . Given that the tunneling current at one point of the surface follows an exponential decay I(z) = I 0 e Àjz , it is possible to relate the modified current I 0 (z), due to relaxations of the surface atoms, to the conductance at this very same point with…”
mentioning
confidence: 99%
“…The interaction between two nondegenerate and/or delocalized electronic states renders the linear relation G / F [19]. The existence of this regime has been unambiguously confirmed by means of AFM/ STM measurements supported by first principles calculations with nonperturbative treatment of the electron transport in metallic atomic point contacts [21].…”
mentioning
confidence: 66%
“…39 in [13]) is κ γ = 12 nm −1 at the β-site and κ γ = 16 nm −1 at sites '1'and '2'. The decay constants for κ I and κ γ are equal within the measurement accuracy, thus the theory by Hofer and Fisher [7] appears to hold for the interaction of W with graphite. The damping signal decays with κ ∆Ets = 20 nm −1 at the β-site and κ ∆Ets = 30 nm −1 at sites '1'and '2' as expected from an energy loss proportional to the square of the attractive force.…”
mentioning
confidence: 89%
“…Chen [5] has found that the square of the attractive energy between tip and sample should be proportional to I with experimental evidence in [6]. Hofer and Fisher [7] suggested that the interaction energy and I should be directly proportional, experimentally found in [8,9]. In this Letter, we investigate the experimental relationships between tunneling currents and conservative as well as dissipative forces for graphite probed with a W tip by performing local spectroscopy on specific lattice sites.…”
mentioning
confidence: 99%